Rapid generation advancement of RIL population and assessing the impact of rhizobium nodulation on crop yields in Chickpea - Nandigam, S.; Mahendrakar, M.D.; Srungarapu, R.; Chand, U.; Gopalakrishnan, S.; Thati, S.; Vatluri, S. R.; Vadlamudi, S.; Vemula, A.K.; Kudapa, H.; Samineni, S. (2025)
Chickpea, a widely cultivated legume, actively fix atmospheric nitrogen in root nodules through a symbiotic relationship with rhizobia bacteria. A recombinant inbred line (RIL) population, progressing from F2 to F7 generations, was developed in a short-period of 18 months using the Rapid Generation Advancement (RGA) protocol. The F7 RILs were evaluated during the 2020-21 and 2021-22 crop seasons under typical field conditions to quantify the effects of nodulation on seed yield (SY) and its associated traits. The analysis of variance revealed a highly significant difference (P < 0.01) among genotypes for seed yield and other agronomic traits, with no significant seasonal effect. In the pooled analysis, nodulating genotypes (NG) exhibited a substantial increase (P < 0.01) in SY (62.55%), 100-seed weight (SW100; 12.21%), harvest index (HI; 6.40%), number of pods per plant (NPPP; 39.55%), and number of seeds per plant (NSPP; 44.37%) compared to non-nodulating genotypes (NNG). Both NG and NNG exhibited a significant (P < 0.01) positive correlation between SY and NPPP (r = 0.64 and 0.63), NSPP (r = 0.66 and 0.61), HI (r = 0.27), and number of primary branches per plant (PBr) (r = 0.31), respectively. The top-performing genotypes for yield and related traits were predominantly nodulating. Genotype-trait bi-plot analysis identified nine nodulating genotypes as the most adaptable across the two seasons—six for SY, plant height, SW100, and three for days to first flowering and maturity. These findings underscore the critical role of nodulation in maximizing chickpea yields and the significant yield penalties associated with non-nodulation. To boost chickpea production, future breeding efforts should focus on developing genotypes with high compatibility with rhizobium strains.